Risk Factor of Vitamin-D Deficiency in Pregnant Women with COVID-19 Infection: Comprehensive Meta-Analysis and Systematic Review - Leny Silviana Farida (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: It has been suggested that coronavirus infection (COVID-19) in pregnant women may be influenced by vitamin D deficiency (VDD). The physiological changes brought on by pregnancy, and the body's partial immune suppression make pregnant women more susceptible to vitamin D deficiency and viral infections. Therefore, this review aims to synthesize the current information on the link between vitamin D levels and the risk of COVID-19 in pregnant women. Material and Methods: A systematic search is conducted in PubMed, ScienceDirect, and Google Scholar. Articles retrieved were screened based on the PRISMA 2020 guidelines. Studies that assessed the effect of vitamin D levels on pregnant women with COVID-19 infection were considered for the review. Odds ratios with their 95 percent confidence intervals (CI) from a meta-analysis using a random-effects model were reported. Results: Three eligible studies were relevant to the relationship between vitamin D deficiency and COVID-19 infection in pregnant women (n=1005). The metanalysis showed that vitamin D deficiency in pregnant women was 1.8 times (95% confidence interval, OR 1.72 to 1.88; p=0.0005) more likely to be infected with COVID-19. Conclusion: According to our results, vitamin D deficiency in pregnant women may increase the risk of COVID-19 infection. Therefore, we recommend adequate vitamin D levels to prevent COVID-19 and its severity.